Papiliomyces puniceum and Metarhizium lymantriidae: two new species from the Gaoligong Mountains in southwestern China - Chen, Zi-Hong; Dai, Yong-Dong; Chen, Kai; Zhang, Yi-Fei; Xu, Ling; Wang, Yuan-Bing (Phytotaxa, 2023)
Two new species, Papiliomyces puniceum and Metarhizium lymantriidae, collected from the Gaoligong Mountains in Baoshan City, Yunnan Province, southwestern China, were determined by both morphological character and multilocus phylogenetic analysis. P. puniceum was confirmed to be phylogenetically related to P. shibinense and P. liangshanense, while obviously separated from them to be a unique lineage. The diagnostic features of P. puniceum were its spherical conidia and puniceus stromata solitarily on the head of Hepialidae larva. M. lymantriidae was the sister species of M. dendrolimatilis, but it was supported as a single distinct lineage. It was apparently distinguished M. lymantriidae from M. dendrolimatilis by its smaller conidia and more slender phialides Moreover, the host of M. lymantriidae was the larva of tussock moth and that of M. dendrolimatilis was the larva of Dendrolimus sp..